PENGARUH GAYA KEPEMIMPINAN KEPALA RUTAN TERHADAP KINERJA PEGAWAI RUTAN KELAS IIB BENGKULU - Muhammad Okto Pazi; Mitro Subroto (Jurnal Komunikasi Hukum, 2022)
The leadership style is said to be good if the leadership style can be properly applied by a leader and can be accepted by employees in the organization, so that the employee's performance can be improved. This study aims to determine and explain the direct influence of leadership style on employee performance in Class IIB Bengkulu prisons. The research method used is the quantitative research method. The population in this study were all employees in class IIB Bengkulu prisons with a total of 66 respondents. The data collection technique in this study was to use a questionnaire. The variable in this study is the independent variable, namely leadership style and the dependent variable, namely performance. Testing the effect of leadership style on employee performance in class IIB Bengkulu detention centers was carried out using validity tests, reliability tests, normality tests and simple regression tests. The results of this study are instrument X producing 14 valid and reliable statements, instrument Y producing 7 valid and reliable statements, based on a significant value of 0.000 <0.05, so it can be concluded that the leadership style variable affects the performance variable.